رجب علی بیگ سرور کے تراجم کا تحقیقی و تنقیدی مطالعہ - Aslam, Dr. Kiran; Ali Shahid, Dr. Rafaqat (Tabeer e Nau, 2025)
Rajab Ali Baig Suroor owns the authorship of remarkable Urdu tale Fasana e Ajaib. He also translated three classic books in Urdu from Persian. The first of them is Suroor e Sultani, translation of Persian semi historical or historical epic, Tarikh e Shamshir Khwani, which is a summarized narrative of Persian glorious epic Shahnama. Suroor’s second translation is Gulzar e Suroor, a literal translated adaptation of famous allegory: Hadaiqul Usshaq of Mulla Razi Tabrezi, and third of this series is a translation of famous Alf Laila Wa Laila into Urdu named Shabistan e Suroor. The last one is actually not a translation but an adaptation of stories and translations of Munshi Abdul Kareem of Lucknow, printed well before Rajab Ali Baig Suroor. The present article elaborates the facts about the classic culture of translation, especially translations in Urdu from Oriental languages. Moreover, Sarroor’s translations have been evaluated. This article highlights some gaps in research on these books and draws some conclusion